UTILIZATION OF VOLUNTARY COUNSELING AND TESTING FOR ACCESSING ANTIRETROVIRAL BY WOMEN OF CHILDBEARING AGE IN WEST PAPUA - Mirna Widiyanti; Setyo Adiningsih; Evi Iriani Natalia; Dedi Ananta Purba; Eva Fitriana (IAKMI South Tangerang Branch, 2021)
Abstract Background: Women of childbearing age living with Human Immunodeficiency Virus (HIV) have many complex problems regarding to their disease and status. They need receiving antiretroviral treatment to optimize health and improve their quality of life by accessing health services. Voluntary Counseling and Testing (VCT) is a health service where antiretroviral treatment can be accessed. Objective: The study aims to analyze the factors which determine the utilization of VCT for accessing antiretroviral treatment by women of childbearing age living with HIV in West Papua. Method: This was an observational, cross-sectional study. The subject was women of childbearing age whose aged 15-49 years old, receiving antiretroviral treatment at VCT of Hospitals in Manokwari, Sorong, and Fakfak. Total were 140 respondents. Data collection was carried out by interview using questionnaire. The data were analyzed statistically by univariate and bivariate using the chi square test. Result: Most of respondents with high intensity in utilization of VCT services were aged 15-35 years, senior high school-university education, unemployment and married status. Demographic and predisposing variables were not significantly associated, but there were associations between enabling factors (distance) with p value=0.00 and reinforcing factor (social support) with p value=0.03 in utilization of VCT services by women of childbearing age in West Papua. Conclusion: Distance and social support are significantly associated with utilization of VCT services by women of childbearing age in West Papua. The easily accessible distance increases their visitation to VCT. In addition, the social support given to them had impact on increasing the utilization of VCT services, and finally these may improve their quality of life. Keywords: women of childbearing age, HIV, antiretroviral, VCT, West Papua Abstrak Latar belakang: Wanita Usia Subur (WUS) dengan status Human Immunodeficiency Virus (HIV) memiliki berbagai masalah yang kompleks terkait dengan penyakit dan statusnya. Kebutuhan pengobatan antiretroviral untuk mengoptimalkan kesehatan dan meningkatkan kualitas hidup dapat mereka peroleh dengan mengakses pelayanan kesehatan. Salah satu layanan untuk mengakses antiretroviral tersebut adalah Voluntary Counseling and Testing (VCT). Tujuan: Tujuan penelitian adalah untuk menganalisis faktor yang menjadi penentu pemanfaatan pelayanan VCT pada wanita usia subur dengan status HIV di Papua Barat. Metode: Jenis penelitian adalah observasional dengan rancangan potong lintang. Unit observasi adalah wanita usia subur yaitu usia 15 -49 tahun, sedang pengobatan antiretroviral di VCT Rumah Sakit Manokwari, Sorong, dan Fakfak. Besar sampel 140 responden wanita usia subur. Pengumpulan data dilakukan dengan wawancara menggunakan kuesioner. Data diolah statistik secara univariat dan bivariat dengan uji chi square. Hasil: Sebagian besar responden dengan intensitas tinggi dalam pemanfaatan pelayanan VCT adalah berusia 15-35 tahun, pendidikan menengah atas-perguruan tinggi, tidak bekerja dan status menikah. Variabel demografi dan predisposisi tidak berhubungan secara statistik dengan pemanfaatan VCT untuk pengobatan antiretroviral, namun ada hubungan antara faktor pemungkin (jarak) dengan nilai p=0,00 dan faktor penguat (dukungan sosial) dengan nilai p =0,03 terhadap pemanfaatan layanan VCT oleh wanita usia subur di Papua Barat. Kesimpulan: Jarak dan dukungan sosial berhubungan secara statistik dengan peningkatan pemanfaatan layanan VCT pada wanita usia subur di Papua Barat. Jarak yang bisa diakses dengan mudah meningkatkan kunjungan pada layanan kesehatan serta dukungan sosial yang diterima wanita yang terinfeksi HIV akan meningkatkan pemanfaatan pelayanan VCT sehingga dapat meningkatkan kualitas hidup. Kata kunci: Wanita Usia Subur, HIV, antiretroviral, VCT, Papua Barat